2015
DOI: 10.1002/jcsm.12007
|View full text |Cite
|
Sign up to set email alerts
|

Preserved muscle oxidative metabolic phenotype in newly diagnosed non‐small cell lung cancer cachexia

Abstract: BackgroundCachexia augments cancer-related mortality and has devastating effects on quality of life. Pre-clinical studies indicate that systemic inflammation-induced loss of muscle oxidative phenotype (OXPHEN) stimulates cancer-induced muscle wasting. The aim of the current proof of concept study is to validate the presence of muscle OXPHEN loss in newly diagnosed patients with lung cancer, especially in those with cachexia.MethodsQuadriceps muscle biopsies of comprehensively phenotyped pre-cachectic (n = 10) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…Insulin sensitivity as well as lipid metabolism are impaired in cancer patients with recent weight loss [7] . However, in lung cancer patients exhibiting significant weight loss muscle oxidative capacity has been reported to be preserved [48] . Further study is needed to determine the relationship between muscle oxidative capacity declines and the specific type of cancer; lung cancer can promote rapid weight loss, which could differentially affect oxidative capacity when compared to less aggressive body weight loss.…”
Section: Skeletal Muscle Oxidative Metabolism and Cancer Cachexiamentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin sensitivity as well as lipid metabolism are impaired in cancer patients with recent weight loss [7] . However, in lung cancer patients exhibiting significant weight loss muscle oxidative capacity has been reported to be preserved [48] . Further study is needed to determine the relationship between muscle oxidative capacity declines and the specific type of cancer; lung cancer can promote rapid weight loss, which could differentially affect oxidative capacity when compared to less aggressive body weight loss.…”
Section: Skeletal Muscle Oxidative Metabolism and Cancer Cachexiamentioning
confidence: 99%
“…Interestingly, in cachectic cancer patients there is evidence for the induction of muscle autophagy-lysosomal processes, while activation of the ubiquitin proteasome system in human cancer patients is more equivocal [122,123,128130] . Also, the link between oxidative metabolism and autophagy is less clear in humans; a decrease in muscle oxidative metabolism has not been reported in some cachectic human cancer patients [48] . As it relates to physical activity, oxidative muscle fibers display higher levels of autophagy flux [131] , and exercise can stimulate autophagy [131133] .…”
Section: Skeletal Muscle Oxidative Metabolism and Cancer Cachexiamentioning
confidence: 99%
See 1 more Smart Citation
“…50 While a significant reduction in the cross-sectional area of muscle fibres was observed in gastrointestinal cancer patients with cachexia and muscle loss, 46,51 Op den Kamp et al found no such change in cachectic patients with advanced non-small-cell lung cancer compared with pre-cachectic patients. 52 Finally, no significant alteration in fibre typing associated with cancer cachexia has been reported in clinical studies, either of gastrointestinal 51,53 or lung 54 cancer.…”
Section: Structure and Typing Of Muscle Fibresmentioning
confidence: 92%
“…71 Op den Kamp et al have also reported an absence of modification of the protein expression of the same markers of mitochondrial biogenesis (PGC1α and TFAM), as well as complexes of the respiratory chain in cachectic patients suffering from pulmonary cancer. 54 On the other hand, Collins et al have observed increased UCP-3 (but not UCP-2) mRNA expression levels in patients with gastrointestinal adenocarcinoma experiencing weight loss. 72 This finding suggests that increased proton leak may contribute to skeletal muscle catabolism through enhancement of energy expenditure.…”
Section: Mitochondrial Metabolismmentioning
confidence: 97%